High mortality in patients presenting with acute pulmonary embolism and elevated INR not on anticoagulant therapy - Wong, Christopher C. Y.; Ng, Austin C. C.; Lau, Jerrett K.; Chow, Vincent; Chen, Vivien; Ng, Arnold C. T.; Yong, Andy S. C.; Sindone, Andrew P.; Marwick, Thomas H.; Kritharides, Leonard (Thrombosis and Haemostasis, 2016)
The prognostic significance of patients presenting with pulmonary embolism (PE) and elevated International Normalised Ratio (INR) not on anticoagulant therapy has not been described. We investigated whether these patients had higher mortality compared to patients with normal INR. A retrospective study of patients admitted to a tertiary hospital with acute PE from 2000 to 2012 was undertaken, with study outcomes tracked using a state-wide death registry. Patients were excluded if they were taking anticoagulants or had inadequate documentation of their INR and medication status. Of the 1,039 patients identified, 94 (9 %) had an elevated INR (> 1.2) in the absence of anticoagulant use. These patients had higher mortality at six months follow-up (26 % vs 6 %, p< 0.001) compared to controls (INR ≤ 1.2). An INR > 1.2 at diagnosis was an independent predictor of death at six months post-PE (hazard ratio [HR] 2.9, 95 % confidence interval [CI] 1.8–4.7, p< 0.001). The addition of INR to a multivariable model that included the simplified pulmonary embolism severity index (sPESI), chest pain, and serum sodium led to a significant net reclassification improvement estimated at 8.1 %. The final model’s C statistic increased significantly by 0.04 (95 % CI 0.01–0.08, p=0.03) to 0.83 compared to sPESI alone (0.79). In summary, patients presenting with acute PE and elevated INR while not on anticoagulant therapy appear to be at high risk of death. Future validation studies in independent cohorts will clarify if this novel finding can be usefully incorporated into clinical decision making in patients with acute PE.
Keywords: International Normalised Ratio; anticoagulant; mortality; prognosis; pulmonary embolism